Consensus Statement on Public Involvement and Engagement with Data-Intensive Health Research - Hassan, Lamiece; Willison, Donald J; Gallacher, Kay; Fitzpatrick, Natalie; Fox, Sarah; Ford, Elizabeth; van Delden, Johannes; Cross, Lynsey; Burgess, Michael; Black, Corri; Banner, Natalie; Cunningham-Burley, Sarah; et al. (International Journal of Population Data Science, 2020)
This consensus statement reflects the deliberations of an international group of stakeholders with a range of expertise in public involvement and engagement (PI&E) relating to data-intensive health research. It sets out eight key principles to establish a secure role for PI&E in and with the research community internationally and ensure best practice in its execution. Our aim is to promote culture change and societal benefits through ensuring a socially responsible trajectory for innovations in this field. Our key premise is that the public should not be characterised as a problem to be overcome but a key part of the solution to establish socially beneficial data-intensive health research for all.